PCSK9 inhibitory activity of marine-derived compounds, aaptaminoids, and benzamide originated from Aaptos aaptos and Acanthaster planci as a potential treatment for atherosclerosis. - Habsah, Mohamad; Muhamad Fadzli, Abd Razak; Nurjannatul Naim, Kamaruddin; Lukman Hakimi, Ab Wahab; Asnuzilawati, Asari; Yosie, Andriani; Siti Fatimah Zaharah, Mohd Fuzi; Jasnizat, Saidin; Mohd Fadhlizil Fasihi, Mohd Aluwi; Jalifah, Latip; Tengku Sifzizul, Tengku Muhammad (Open Science Publishers LLP Inc., 2020)
Atherosclerosis is an inflammatory disorder of the vasculature and one of the underlying causes of cardiovascular diseases. Numerous preventative and therapeutic approaches are being explored to limit the morbidity and mortality of this disease. Nevertheless, some of the treatments cost greatly and contributed to various side effects; for example, statin therapy is associated with substantial residual cardiovascular risk as well as issues such as tolerability and patientdependent efficacy. Currently, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor has been attracting interests in the drug discovery of atherosclerosis treatment, but ezetimibe, a successful PCSK9 inhibitor, is an expensive monoclonal antibody. Thus, exploring new PCSK9 inhibitors is crucial in overcoming this constraint. In the previous work, aaptaminoids and methyl benzoate were isolated from marine sponges Aaptos aaptos and Acanthaster planci, respectively. These compounds enhance the transcription of the peroxisome proliferator-activated receptor gamma (PPARγ) in the luciferase assay. PPARγ agonist was hypothesized to inhibit the expression of the PCSK9 gene because the former is a transcription factor toward the latter. The synthesis of three aaptaminoids and 11 methyl benzoate derivative was carried out to address its potential as a PCSK9 inhibitor. The structure of the synthesized compound was elucidated using nuclear magnetic resonance spectral and electron impact mass spectral data. The PCSK9 inhibitory activities were determined by luciferase assay. Four aaptaminoids, such as aaptamine, N1 ,N4 -bisbenzylaaptamine, N4 -[(3,4,5-trimethoxy)benzyl]aaptamine, and N1 -[(3,4,5- trimethoxy)benzyl]aaptamine, and one benzamide derivative, N-(2,3-dihydro-1H-inden-2-yl)-2-methoxybenzamide, were found to inhibit the expression of PCSK9 gene.